Penerapan Label Pangan pada Produk Bagiak oleh Produsen di Banyuwangi - Zhiana Chairun Nikmah; Ririh Yudhastuti; Desak Made Sintha Kurnia Dewi (Dian Nuswantoro Semarang, 2018)
Food packaging that provides food labels to inform consumers about product quality. Food labeling is done with the aim of providing a sense of security to consumers without having to open the product packaging. Supervision conducted by the Department of Industry and Trade and the Health Service in 12 sub-districts in Banyuwangi district, industrial owners do not have PIRT and do not know the food label conditions. This can increase the potential for insecurity and insecure quality. Packaging food from Banyuwangi area is for the production of home industry in the form of packaging. The objective of the study was to evaluate food labels in household industries that produce diets in Banyuwangi.The research design is cross sectional with observation method in 12 household industries conducted at the Trade Industry Service of Banyuwangi Regency. The data collection used a questionnaire survey on the results of an industrial sample. Descriptive data analysis, presented in proportion to tables and narratives. The results obtained 50% of 12 household products have met the minimum label criteria in accordance with Government Regulation No.69 of 1999 on Food Label and Advertisement. The lower inclusion of the manufacturer's name and address affects the product in the completeness of the label attribute.